Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan di Kantor Pos Cabang Utama Kota Bandung - Irgiansyah, Ilhan; Pramanik, Nuniek Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The main goal of the study is to look into and evaluate how leadership styles affect how well employees perform at the Bandung City Main Branch Post Office. This study uses a descriptive methodology and a quantitative approach. Field research projects, surveys, and in-depth literature reviews are all used to collect data. The SPSS (Statistical Product and Service Solutions) programme, version 29, is used to analyse the gathered data. Validity, reliability, normalcy, heteroskedasticity, linearity, simple linear regression, t-tests, and the coefficient of determination are all included in the completed assessments. This study also shows how aspects of leadership styles such as accountability, communication skills, and decision-making capacity have a big impact on worker performance. The results of the t-test, where the computed t-value exceeds the tabulated t-value, namely 6.027 > 2.048, support this conclusion. Therefore, it can be concluded that variable X does in fact have an impact on variable Y. Keywords: Post Office, Leadership Style, Employee Performance, SPSS version 29